Method for producing luminescent nanoparticle dispersion, luminescent nanoparticle polymer ink and luminescent nanoparticle dispersion member
Patent Information
- Application Number
- JP2023139342
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2025-03-13
AI Technical Summary
【0020】 本発明によれば、発光性ナノ粒子分散液の製造工程において、粗ナノ粒子の再分散に用いる分散媒として、分散媒の分散力エネルギー(δdSol)と発光性ナノ粒子の分散力エネルギー(δdLN)との差の2乗(δdSol-δdLN)2が3.0MPa以下と、小さい分散媒を用いることで、沈降分離時にナノ粒子の再凝集が抑制され、分級で粗大粒子のみを除去することができるため、分散安定性およびPLQYの両面が向上した発光性ナノ粒子分散液を製造することができる。前記製造工程において、発光性ナノ粒子前駆体、有機塩基化合物、および有機酸化合物の種類および量を変更して、得られる発光性ナノ粒子の組成を調整することにより、紫外線等の励起光照射下に多様な色(赤、黄、緑、青など)を示す発光性ナノ粒子分散液を製造することができる。
Smart Images

Figure 2025033558000005 
Figure 2025033558000006 
Figure 2025033558000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a luminescent nanoparticle dispersion having excellent dispersion stability and a high photoluminescence quantum yield (PLQY). [Background technology]
[0002] Luminescent nanoparticles have a very small particle size and unique optical and electronic properties that follow quantum mechanics different from those of bulk particles, and are expected to be applied to highly functional materials. In particular, luminescent nanoparticles have become important materials that can realize optical devices such as light-emitting diodes (LEDs), optical amplifiers, single-photon sources, and solar cells by significantly improving the electrical and optical properties by adjusting the shape and particle size of quantum dots, focusing on the quantum confinement effect and particle size dependence.
[0003] Luminescent nanoparticles have a large specific surface area, so they can easily become soft-aggregated. It is known that soft-aggregated particles are removed together with coarse particles during the classification process during the manufacturing process, resulting in a decrease in yield, or that if they remain in a soft-aggregated state for a long time, they will coagulate and change to the same optical properties as bulk particles, causing variation in the optical properties of the entire dispersion. Therefore, it is important to control the interfacial phenomenon on the particle surface.
[0004] In the synthesis of luminescent nanoparticles and their application, the affinity and high dispersibility of the luminescent nanoparticles in a solvent are the most important issues. Regarding the dispersibility of luminescent nanoparticles in a solvent, there is a report of a modified organic pigment obtained by reacting a pigment with a surface-active compound selected based on the Hansen Solubility Parameter (HSP) (Patent Document 1). The HSP has three parameters that contribute to the cohesive energy density of a compound: a dispersion component (δd) that describes hydrophobicity, a polar component (δp), and a hydrogen bond component (δh). In Patent Document 1, the software HSPiP is used to calculate a Hansen space in which these three parameters are visualized as coordinates, and a material near the center of the Hansen space is selected as a surface-active compound, thereby improving the dispersibility and coloring power of the organic pigment.
[0005] It has also been reported that in a paste-like resin composition containing silver-containing particles, a solvent, and a thermosetting resin, the electrical conductivity of the resulting material was improved by adjusting the difference between the Hansen solubility parameter (HSP) of the silver-containing particles and the Hansen solubility parameter (HSP) of the solvent to 4.3 to 9.8 (Patent Document 2).
[0006] It has been reported that, using the Hansen dissolving sphere method, the HSP value changes before and after applying a silane coupling treatment to the surface of metal particles, and dispersibility in a specific medium is achieved by changing the state of the metal particle surface in contact with the solvent (Non-Patent Document 1).
[0007] Various methods have been proposed for synthesizing luminescent nanoparticles, but liquid-phase synthesis is mainly used for economic reasons. For example, in the synthesis of perovskite quantum dots, the ligands are coordinated to the quantum dot surface by adding ligands, which simultaneously suppresses surface defects and improves dispersion stability.
[0008] However, even if the same ligand is coordinated to the luminescent nanoparticles, if an arbitrary dispersion medium is selected to prepare the luminescent nanoparticle dispersion, the effect of the ligand changes significantly, affecting the dispersibility. PL It is known that this causes various problems, such as changes in the composition of the raw material over time and a decrease in yield due to coagulation and sedimentation. For this reason, there is a demand for a method for producing a dispersion of luminescent nanoparticles having high dispersibility. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2019-026835 A [Patent Document 2] Patent Publication No. 2022-018051 [Non-patent literature]
[0010] [Non-Patent Document 1] Nobuyuki Fujiwara, Shunsuke Imai and Hideki Yamamoto, Mater. Chem. Phys. 2019, 229, 139-148 Summary of the Invention [Problem to be solved by the invention]
[0011] In the present invention, the dispersion force energy (δd Sol ) and the dispersion energy of the luminescent nanoparticles (δd LN ) and the square of the difference (δd Sol -δd LN ) 2 The present invention provides a method for producing a luminescent nanoparticle dispersion liquid that maintains high dispersibility while suppressing re-aggregation of luminescent nanoparticles and suppressing a decrease in PLQY by using a dispersion medium with a small particle size. [Means for solving the problem]
[0012] The present invention comprises the following: [1] A process 1 in which a luminescent nanoparticle precursor, an organic base compound, and an organic acid compound are mixed in an organic solvent to synthesize a crude nanoparticle solution in the liquid phase, and then the organic solvent is removed from the crude nanoparticle solution by precipitation separation to obtain crude nanoparticles; Sol ) and the dispersion energy of the luminescent nanoparticles (δd LN ) and the square of the difference (δd Sol -δd LN ) 2 and step 2 of adding a dispersion medium having a viscosity of 3.0 MPa or less to redisperse the coarse nanoparticles, and then removing coarse particles by classification.
[0013] [2] The method for producing a luminescent nanoparticle dispersion liquid according to [1], characterized in that in step 2, one or more of an organic base compound, an organic acid compound, and a metal halide are dissolved in the dispersion medium.
[0014] [3] The method for producing a luminescent nanoparticle dispersion liquid according to [1] or [2], wherein the dispersion medium in the step 2 is a non-polar solvent having an alicyclic hydrocarbon skeleton.
[0015] [4] The method for producing a luminescent nanoparticle dispersion liquid according to [1] or [2], wherein the non-polar solvent having an alicyclic hydrocarbon skeleton is one or more of cyclohexane, methylcyclohexane, and decalin.
[0016] [5] The method for producing a luminescent nanoparticle dispersion liquid according to [1] or [2], wherein the luminescent nanoparticles are metal halide perovskite.
[0017] [6] The method for producing a luminescent nanoparticle dispersion liquid according to [1] or [2], wherein the luminescent nanoparticles have a particle size of 1 to 30 nm.
[0018] [7] A luminescent nanoparticle polymer ink, comprising a luminescent nanoparticle dispersion liquid obtained by the method according to [1] or [2] above and a polymer dissolved therein.
[0019] [8] A luminescent nanoparticle dispersion member formed using the luminescent nanoparticle polymer ink described in [7]. Effect of the Invention
[0020] According to the present invention, in the manufacturing process of the luminescent nanoparticle dispersion, the dispersion medium used for redispersing the crude nanoparticles has a dispersion force energy (δd Sol ) and the dispersion energy of the luminescent nanoparticles (δd LN ) and the square of the difference (δd Sol -δd LN ) 2By using a dispersion medium with a low viscosity of 3.0 MPa or less, re-aggregation of nanoparticles is suppressed during sedimentation and only coarse particles can be removed by classification, making it possible to produce a luminescent nanoparticle dispersion with improved dispersion stability and PLQY. In the above production process, by changing the types and amounts of the luminescent nanoparticle precursor, organic base compound, and organic acid compound to adjust the composition of the obtained luminescent nanoparticles, it is possible to produce a luminescent nanoparticle dispersion that exhibits a variety of colors (red, yellow, green, blue, etc.) when irradiated with excitation light such as ultraviolet light. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a diagram showing an example of a production process of the luminescent nanoparticle dispersion of the present invention by the LARP method. [Diagram 2] FIG. 2a illustrates a process for forming conventional perovskite quantum dots, and FIG. 2b illustrates a process for forming a luminescent nanoparticle dispersion according to the present invention. [Diagram 3] FIG. 3 is a graph showing the change in yield versus (δdSol-δdLN) 2 . [Figure 4] 4 is a graph showing the particle size distribution before classification, after classification (sediment), and after classification (supernatant) in Comparative Example 1. The supernatant after classification is collected to produce a luminescent nanoparticle dispersion. [Diagram 5] FIG. 5 is a graph showing the absorption spectra of the luminescent nanoparticle dispersion members prepared using the fluorescent nanoparticle dispersion liquids of Example 14 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] [Method of manufacturing luminescent nanoparticle dispersion] The method for producing a luminescent nanoparticle dispersion of the present invention includes a step 1 of synthesizing a crude nanoparticle solution in liquid phase by mixing a luminescent nanoparticle precursor, an organic base compound, and an organic acid compound in an organic solvent, and then removing the organic solvent from the crude nanoparticle solution by sedimentation to obtain crude nanoparticles; Sol) and the dispersion energy of the luminescent nanoparticles (δd LN ) and the square of the difference (δd Sol -δd LN ) 2 and step 2 of adding a dispersion medium having a viscosity of 3.0 MPa or less to redisperse the coarse nanoparticles, and then removing coarse particles by classification.
[0023] The luminescent nanoparticle dispersion of the present invention can be produced by the ligand-assisted reprecipitation (LARP) method, the hot injection method, the mechanochemical method, the ultrasonic bead mill method, the microflow reactor method, the forced thin film flow reactor method, and the like, as long as it includes the above-mentioned steps 1 and 2. However, the LARP method is preferred in terms of simplicity and high versatility. Therefore, in the present invention, a method for producing a perovskite quantum dot complex using the LARP method will be described.
[0024] Luminescent nanoparticles include those that emit light using ionizing or non-ionizing radiation or chemical reactions as an excitation source, those that emit light due to stress, etc. Specific examples include crystals made of metal halides with a particle size of several to several tens of nm that absorb excitation light and emit fluorescence or phosphorescence.
[0025] The luminescent nanoparticles of the present invention are nanoscale semiconductor particles that absorb photons or electrons with energy greater than the band gap (the energy difference between the valence band and the conduction band) and emit light with a wavelength according to the particle size. As long as the nanoparticles have the function of luminescent nanoparticles, their structure and components are not particularly limited, but in an embodiment of the present invention, the luminescent nanoparticles are surface-modified with ligands on the nanoparticle surface.
[0026] The elements contained in the luminescent material of the luminescent nanoparticles are not particularly limited as long as they are quantum dot particles that exhibit an emission wavelength in the visible light wavelength region, and examples thereof include perovskite compounds, II-VI compounds, III-V compounds, IV-VI compounds, and combinations thereof. These can be used alone or in combination of two or more types in any ratio.
[0027] Specific examples of the II-VI group compounds include CdSe, CdS, ZnS, CdSeS, and CdZnSeS. Specific examples of the III-V group compounds include InP, GaN, GaP, AlN, InNP, and GaInNP. Specific examples of the IV-VI group compounds include SnS, PbS, PbSe, SnPbS, and SnPbSSe. Specific examples of the IV group compounds include Se, Ge, and SiC. At least one compound selected from the mixtures of these compounds may be used.
[0028] The perovskite compound has the general formula A p B q X r A is an organic and / or inorganic monovalent cation occupying the A site, B is a metal cation occupying the B site, X is a monovalent anion occupying the X site, B is surrounded by X in an octahedral shape, and the octahedra share X at their vertices to form a perovskite structure. p is an integer of 1 or more and 4 or less, q is 1 or 2, and r is an integer of 3 or more and 9 or less. The integers are selected to satisfy the following formula. p + (2 × q) = r
[0029] The luminescent nanoparticles of the present embodiment are perovskite-type luminescent nanoparticles represented by the general formula ABX3. Among luminescent nanoparticles, perovskite-type luminescent nanoparticles are preferred because they have excellent optical and electronic properties and can be easily synthesized from a solution process.
[0030] The monovalent organic cations that occupy the A site are primary, secondary, and quaternary ammonium ions, formamidinium ions (CH(NH2)2 + ;FA), guanidinium ion ((H2N)2C=NH2 + ;GA), imidazolium ion, 1-methylimidazolium ion, pyridinium ion, 1-methylpyridinium ion, pyrrolidinium ion, and thiouronium ion.
[0031] Specific examples of primary to quaternary ammonium ions are ammonium ion (NH4 + ), methylammonium ion (CH3NH3 + ;MA), dimethylammonium ion, ethylammonium ion (CH3CH2NH3 + ;EA), diethylammonium ion, propylammonium ion, isopropylammonium ion, butylammonium ion, isobutylammonium ion, t-butylammonium ion, benzylammonium ion and phenethylammonium ion. Of these, methylammonium ion is preferred.
[0032] The monovalent inorganic cations are the alkali metal ions: cesium, rubidium, potassium, sodium and lithium.
[0033] Among these, from the viewpoint of the crystal structure tolerance factor (TF), it is preferable that 60 mol % or more, preferably 70 mol % or more, more preferably 80 mol % or more of the A site cations in ABX3 are at least one kind of cation selected from the group consisting of cesium ion, rubidium ion, MA, EA, FA and GA. A may be only one kind or may be two or more kinds.
[0034] The metal cations occupying the B site include lead ions, germanium ions, tin ions, antimony ions, bismuth ions, copper ions, nickel ions, cobalt ions, iron ions, manganese ions, chromium ions, cadmium ions, europium ions, ytterbium ions, silver ions, and palladium ions. Of these, lead ions and tin ions are preferred. In addition, antimony ions, bismuth ions, copper ions, nickel ions, cobalt ions, iron ions, manganese ions, chromium ions, cadmium ions, europium ions, ytterbium ions, and silver ions may be included within the range of 5% or less of element ratios of lead ions and tin ions. B may be only one type, or may be two or more types.
[0035] The monovalent anion occupying the X site is the cyanide ion (CN - ), thiocyanide ion (SCN - ), isothiocyanide ion (NSC - ), thiolate ion (S - ) and halide ions. Halide ions are chloride, bromide and iodide ions. ABX3 can contain one or more X's.
[0036] A, B and X can be appropriately selected taking into consideration the energy band gap of the luminescent nanoparticles and the sizes of A, B and X.
[0037] Specific examples of preferred perovskite type compounds include the following compounds, however, the present invention is not limited to the following specific examples of perovskite type compounds. A specific example of ABX3 is Cs a1 MA a2 EA a3 FA a4 GA a5 K a6 Rb (1-a1-a2-a3-a4-a5-a6) Pb b1 Sn b2 Ge (1-b1-b2) (Cl (1-y-z) Br y I z )3(0≦a1≦1, 0≦a2≦1, 0≦a3≦1, 0≦a4≦1, 0≦a5≦1, 0≦a6≦1, a1+a2+a3+a4+a5+a6≦1, 0≦b1≦1, 0≦b2≦1, b1+b2≦1, 0≦y≦1, 0≦z≦1, y+z≦1). In order for the crystal structure of ABX3, which has a perovskite structure, to be stable, the TF must be in the range of 0.70 to 1.10. Examples of such compounds include CsPbBr3 (TF = 0.86), FAPbBr3 (TF = 1.01), CsPbI3 (TF = 0.85), and CsSnI3 (TF = 0.92).
[0038] The structure of the compound that is the light-emitting portion of the luminescent nanoparticles may be a homogeneous structure consisting of one type of compound, a core-shell structure consisting of two or more types of compounds, or a gradient structure that has a gradation in composition from the outermost surface to the inside of the particle. For example, when InP is used as the core material, ZnS or the like is used as the shell.
[0039] The average particle size of the luminescent nanoparticles is not particularly limited as long as it is within a range in which it can function as a luminescent material. The average particle size is preferably 1.0 to 30 nm or less, more preferably 2.0 to 20 nm, and particularly preferably 4.0 to 16 nm, as the particle size of the primary particles. If the average particle size is within the range, the quantum confinement effect is exerted, and a high PLQY is exerted, while at the same time, the sedimentation rate is sufficiently slowed down, and dispersion stability can be imparted.
[0040] The shape of the luminescent nanoparticles is not particularly limited. Examples include spherical, cubic, cylindrical, polyhedral, and scaly shapes. Among these, from the viewpoints of dispersion stability and crystal lattice distortion within the particles, it is preferable that the nanoparticles are either spherical or cubic, or both.
[0041] In step 1, the precursor of the luminescent nanoparticles, an organic base compound, and an organic acid compound are mixed in an organic solvent to synthesize a crude nanoparticle solution in the liquid phase, and then the organic solvent is removed from the crude nanoparticle solution by sedimentation to obtain crude nanoparticles. Specifically, the precursor of the luminescent nanoparticles is dissolved in an organic solvent to prepare a precursor solution of perovskite quantum dots. An organic acid compound and an organic base compound are dissolved in an organic solvent of a different type from the precursor solution, stirred and mixed, and the precursor solution is injected to precipitate perovskite quantum dots, thereby obtaining a crude nanoparticle solution. This is then subjected to sedimentation separation using a centrifuge, and the liquid phase is removed to obtain crude nanoparticles. Figure 1 shows the flow of step 1 (top).
[0042] The luminescent nanoparticle precursor comprises a compound containing an organic and / or inorganic monovalent cation (hereinafter also simply referred to as "monovalent cation") occupying the A site in the general formula ABX3, a compound containing a divalent metal cation occupying the B site, and a compound containing a monovalent anion occupying the X site.
[0043] An example of a compound containing a monovalent cation occupying the A site is a compound consisting of the monovalent cation and X. When the monovalent cation is an inorganic cation, specifically an alkali metal ion, the compound containing the monovalent cation is a salt of the alkali metal ion and X. In this case, X is a halide ion, carbonate ion, acetate ion, or the like, and a halide ion is preferred.
[0044] When the monovalent cation is an organic cation, the compound containing the monovalent cation is a salt of an alkali metal ion and X. Specific examples include ammonium halide salts such as methylammonium bromide, and formamidinium halide salts such as formamidinium bromide.
[0045] Compounds containing a divalent metal cation occupying the B site include halides of germanium ion, tin ion, lead ion, antimony ion, or bismuth ion. The halides are chloride, bromide, or iodide. Specific examples include lead(II) bromide (PbBr2), lead(II) iodide (PbI2), lead(II) chloride (PbCl2), tin(II) bromide (SnBr2), tin(II) iodide (SnI2), tin(II) chloride (SnCl2), germanium(II) bromide (GeBr2), germanium(II) iodide (GeI2), and germanium(II) chloride (GeCl2). These compounds can be used alone or in combination of two or more in any ratio.
[0046] Compounds containing a monovalent anion occupying the X site include compounds comprising the monovalent anion and the above-mentioned monovalent cation occupying the A site or a divalent metal cation occupying the B site, as well as hydrogen chloride and hydrogen iodide.
[0047] The organic base compound may be any of aliphatic amines, aromatic amines, and quaternary ammonium salts. Specifically, examples of the organic base compound include aliphatic amines having 3 to 24 carbon atoms, such as oleylamine, propylamine, butylamine, pentylamine, octylamine, hexadecylamine, octadecylamine, 2-hexyldecane-1-amine, 2-decyltetradecane-1-amine, stearylamine, and cyclohexylamine; aniline, benzylamine, phenethylamine, 3-phenyl-2-propene-1-amine, phenylmethyl ... aromatic amines having 6 to 34 carbon atoms, such as naphthylamine, 2,2'-iminodibenzoic acid, 3-phenylpropylamine, 4-phenylbutylamine, naphthylamine, 4-aminobiphenyl, and 3,4,5-tris(prop-2-en-1-yloxy)benzylamine; and quaternary ammonium salts, such as didecyldimethylammonium salts, benzyltrimethylammonium bromide salts, 3-(N,N-dimethyloctadecylammonio)propanesulfonate salts, and stearyltrimethylammonium salts. These compounds can be used alone or in combination of two or more at any ratio.
[0048] The organic acid compounds include organic carboxylic acids, organic sulfonic acids, organic sulfinic acids, and phosphorus oxo acid compounds (organic phosphonic acids, organic phosphonates, organic phosphinic acids). For example, organic carboxylic acids such as oleic acid, stearic acid, palmitic acid, glutaric acid, sebacic acid, benzoic acid, and 3,4,5-tri(2-propenoxy)benzoic acid; organic sulfinic acids such as benzenesulfinic acid; organic phosphonic acids such as octylphosphonic acid, tetradecylphosphonic acid, and tri-n-octylphosphine oxide; and organic phosphinic acids such as di-t-octylphosphinic acid and diisooxylphosphinic acid. These compounds can be used alone or in combination of two or more at any ratio.
[0049] Both organic base compounds and organic acid compounds form coordinate bonds mainly with B in the general formula ABX3, and act to both uniformize particle size and compensate for surface defects when producing luminescent perovskite nanoparticles. The addition of both organic base compounds and organic acid compounds improves both the yield and PLQY of the luminescent nanoparticle dispersion. When the surface of the luminescent nanoparticles is modified with the long chains of the organic base compounds or organic acid compounds, this site acts to adjust the particle growth and uniform the particle size.
[0050] The average particle size of the primary particles of luminescent nanoparticles is determined by the maximum wavelength (λ PL ) can be obtained. For example, in the case of CsPbBr3, when the average particle size is 2.6 nm, the maximum wavelength of photoluminescence (PL) is PL ) is 450 nm, and the average particle size is 6.2 nm, λ PL When the average particle size is 15 nm and the λ PL The particle size of the primary particles of the luminescent nanoparticles affects the properties of the luminescent nanoparticle dispersion, as shown in Fig. 1. Therefore, by appropriately combining the composition of ABX3, the types and addition ratios of the organic base compound and the organic acid compound, it is possible to shift the maximum wavelength of the emission spectrum to a desired wavelength, or to change the half width (FWHM) of the emission peak. PL ) can be made smaller.
[0051] The organic solvent used in step 1 may be a solvent (good solvent) that has high solubility for the luminescent nanoparticle precursor, the organic base compound, and the organic acid compound, and is preferably an aprotic polar solvent that is miscible with the nonpolar solvent. Specifically, N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), acetonitrile, etc. are used.
[0052] Luminescent nanoparticle precursors, organic base compounds, and organic acid compounds are mixed in an organic solvent to synthesize a crude nanoparticle solution in the liquid phase, and then the organic solvent is removed from the crude nanoparticle solution by sedimentation to obtain crude nanoparticles. Sedimentation is usually performed by centrifugation. In step 1, there is loss of unreacted luminescent nanoparticle precursors and products that do not settle during sedimentation, but the yield is still high, at 85-90%.
[0053] In step 2, the crude nanoparticles recovered in step 1 are subjected to the dispersion force energy of the dispersion medium (δd Sol ) and the dispersion energy of the luminescent nanoparticles (δd LN ) and the square of the difference (δd Sol -δd LN ) 2 A dispersion medium having a pressure of 3.0 MPa or less is added to redisperse the coarse nanoparticles, and then the coarse particles are removed by classification. Figure 1 shows the flow of step 2 (lower part).
[0054] (δd Sol -δd LN ) 2 In other words, the dispersion force energy of the dispersion medium (δd Sol ) and the dispersion energy of the luminescent nanoparticles (δd LN ) is small, which means that the luminescent nanoparticles and the dispersion medium interact to the same extent. (δd Sol -δd LN ) 2 It is believed that the smaller the σ, the greater the wettability between the ligands on the surface of the crude nanoparticles and the dispersion medium, and the more the ligands orient themselves toward the dispersion medium, improving dispersibility. If redispersion is performed in this state, reagglomeration is suppressed, and the decrease in yield due to classification can be suppressed.
[0055] In order to obtain high yield improvement due to high dispersibility, (δd Sol -δd LN ) 2 is 3.0 MPa or less, preferably 2.0 MPa or less, more preferably 1.5 MPa or less, and most preferably 0.5 MPa or less.
[0056] Here, the dispersion force energy (δd Sol ) is one of the three parameters used to represent the Hansen coordinates in three-dimensional space in the Hansen Solubility Parameter (HSP), which evaluates the solubility of a substance.
[0057] Hansen solubility parameters (HSP) are based on the idea that "two substances with similar intermolecular interactions are easily dissolved in each other," and divide the interaction between a solute and a solvent into three components: dispersion, polarity, and hydrogen bonding, and express them as the energy due to intermolecular forces between molecules (δd), the energy due to dipole interactions between molecules (δp), and the energy due to hydrogen bonds between molecules (δh), respectively. The units of δd, δp, and δh are all in MPa. 0.5 When the HSPs of two substances are in Hansen space, they tend to dissolve in each other if the distance between the two points is close.
[0058] Hansen solubility parameters are often used to predict the solubility of polymers in organic solvents. Although dispersion or aggregation of nanoparticles in a solvent is not dissolution, it is thought that the surface free energy of nanoparticles changes as the wettability of the ligands on the particle surface changes with the solvent, which changes the tendency for the nanoparticles to aggregate. In other words, regardless of the type of compound in the luminescent nanoparticles, the dispersibility is determined by the state of the ligands and the dispersion medium.
[0059] When the inventors analyzed the dispersibility of luminescent nanoparticles, the dispersion force energy (δd Sol ) and the dispersion energy of the luminescent nanoparticles (δd LN ) the smaller the difference, the better the dispersibility. Luminescent nanoparticles have ligands on their surfaces, and the δd LN Although the amount of re-agglomeration changes, the amount of re-agglomeration can be determined by controlling the difference in dispersion force energy, and it has become possible to arbitrarily select a dispersion medium with high dispersion stability.
[0060] δd of luminescent nanoparticles LNcan be obtained using analysis software. The analysis software that can be used is HSPiP version 5.4.08. Details of HSPiP are described at https: / / www.hansen-solubility.com. Note that, even if it is not the above analysis software, other software using the same measurement principle or different versions of HSPiP can be used to calculate δd LN You may ask for:
[0061] At least 14 pure solvents with known Hansen solubility parameters are used as evaluation solvents, and the crude nanoparticles are redispersed in the evaluation solvent. The dispersion state at this time is scored, and the score is entered into the analysis software to obtain δd LN can be sought.
[0062] In organic acid compounds and organic base compounds, which are generally used as ligands for luminescent nanoparticles, the dissociated portion is coordinated to the particle surface, and the alkyl portion or aromatic hydrocarbon portion is coordinated in contact with the dispersion medium. Therefore, the dispersion force energy of the dispersion medium (δd Sol ) and the dispersion energy of the luminescent nanoparticles (δd LN ) and the square of the difference (δd Sol -δd LN ) 2The dispersion medium having a viscosity of 3.0 MPa or less is preferably an organic solvent having low polarity other than halogen. Dispersion media that satisfy such requirements include pentane, cyclopentane, hexane, cyclohexane, heptane, cycloheptane, 1-hexene, cis-2-hexene, trans-2-hexene, cis-3-hexene, trans-3-hexene, 3,3-dimethyl-1-butene, cyclohexene, cycloheptene, octane, nonane, decane, cyclopropane, cyclobutane, cyclooctane, decalin, norbonane, methylcyclohexane, methylcyclohexene, 1,1-dimethylcyclohexane, cis-1,2-dimethylcyclohexane, and cis-1,3-dimethylcyclohexane. , trans-1,3-dimethylcyclohexane, cis-1,4-dimethylcyclohexane, trans-1,4-dimethylcyclohexane, 1,2,4,5-tetramethylcyclohexane, 1,1,3,3,5-pentamethylcyclohexane, (cyclopentylmethyl)cyclohexane, dicyclohexylmethane, 1-ethyl-2-propylcyclohexane, amylcyclohexane, 1,1'-ethylenebiscyclohexane, isobutylcyclohexane, o-xylene, m-xylene, p-xylene, chloroform, triethylamine, carbon tetrachloride, and diethyl ether. These may be used alone or in combination of two or more in any ratio. Among the above dispersion media, alicyclic saturated hydrocarbon solvents composed only of carbon are more preferred, and cyclohexane, methylcyclohexane, and decalin are particularly preferred from the viewpoint of ease of availability and handling.
[0063] The dispersion energy in a mixed solvent can be calculated from the volume ratio of the mixed solvents. For example, toluene (δd sol =18.0MPa 0.5 ) and cyclohexane (δd sol =16.8MPa 0.5 The dispersion energy of a mixed solvent in which the two solvents are mixed in a volume ratio of 1:1 is δd sol =17.4MPa 0.5 It becomes.
[0064] In addition to the dispersibility of the luminescent nanoparticles due to wetting, the dispersion medium also affects the dissociation constant of the weak acid or weak base of the ligand coordinated to the particle surface. Some dispersion media improve the dispersibility of the luminescent nanoparticle dispersion, but some reduce the PLQY due to the detachment of the ligand. Therefore, an organic base compound, an organic acid compound, or an inorganic halide (hereinafter also referred to as a "ligand compound") that serves as a ligand may be added at the same time as the dispersion medium. Any one of the organic base compound, the organic acid compound, and the inorganic halide may be used alone, or two or more types may be added at any ratio. A compound different from the organic base compound and the organic acid compound used in step 1 may be used. The ligand compound may be added at the same time as the dispersion medium, but it is preferable to dissolve the ligand compound in the dispersion medium in advance in order to mix it with the crude nanocrystals in a short time.
[0065] There is no limit to the concentration of the ligand added simultaneously with the dispersion medium, as long as the concentration is equal to or less than the concentration at which the ligand is completely dissolved in the dispersion medium. In general, the amount of the ligand (the total of the organic base compound, the organic acid compound, and the inorganic halide) added is preferably 1000 mmol / L or less, more preferably 500 mmol / L or less, and particularly preferably 150 mmol / L or less relative to the dispersion medium.
[0066] In step 2, the dispersion medium is added to the coarse nanoparticles to redisperse them, and then coarse particles are removed by classification. There are no particular limitations on the classification method as long as it can remove coarse particles to leave only particles with a predetermined diameter or less and can improve the fluidity of the particles by aligning the particle size distribution, but centrifugation using a centrifugal classifier is preferred in terms of efficient classification.
[0067] The concentration of the luminescent nanoparticles in the luminescent nanoparticle dispersion obtained in step 2 is usually 0.01 to 100 mg / mL, preferably 0.1 to 50 mg / mL, and more preferably 0.5 to 20 mg / mL. The concentration can be measured by setting an integrating sphere on a fluorescence spectrophotometer FP-8600 (manufactured by JASCO Corporation; excitation wavelength 370 nm), and calculating the luminescent nanoparticle concentration from the dilution ratio at which the absorptivity of the luminescent nanoparticle dispersion becomes 0.5.
[0068] As shown in the following formula, the ratio of the amount of perovskite quantum dots (PeQD) calculated from the concentration of the luminescent nanoparticles to the amount of PeQD in the precursor solution is defined as the yield (%), where the amount of PeQD represents the concentration of the luminescent nanoparticles.
number
[0069] The average particle size of the luminescent nanoparticles in the luminescent nanoparticle dispersion is usually 1 to 30 nm, preferably 2 to 20 nm. The average particle size of the luminescent nanoparticles is determined by measuring λ PL It can be obtained from. When the average particle size of the luminescent nanoparticles is within the above range, the luminescent nanoparticle dispersion has high dispersibility. If the particle size of the luminescent nanoparticles is extremely small, Ostwald ripening and aggregation are promoted, making it difficult to maintain the crystal structure. In addition, the emission wavelength becomes large due to the quantum size effect. On the other hand, if the particle size is extremely large, the stability of the excitons during excitation decreases, and the PLQY decreases.
[0070] The luminescent nanoparticles emit light in the visible to near infrared wavelength range (300 to 1000 nm). The light emission may be due to optical excitation or electrical excitation. When the light emission is due to optical excitation, the wavelength of the excitation light is 200 to 800 nm, specifically 250 to 750 nm, more specifically 400 to 700 nm.
[0071] [Luminescent nanoparticle polymer ink] The luminescent nanoparticle polymer ink of the present invention is a polymer ink in which a polymer is dissolved in the luminescent nanoparticle dispersion liquid.
[0072] The polymer may be either a thermoplastic resin or a thermosetting resin. The thermosetting resin may be a photocurable resin that is cured by ultraviolet light in addition to heat curing, or may be a mixture of a thermosetting resin and a photocurable resin. The photocurable resin is preferably a resin that contains both a site having a cycloalkane or aromatic ring as a hydrophobic part and an acrylic group, an epoxy group, or the like as a curable part. A thermoplastic resin is usually used for the luminescent nanoparticle polymer ink.
[0073] The thermoplastic resin is not particularly limited as long as it transmits visible light, and examples thereof include acrylic resin, PET, polycarbonate, polystyrene resin, polyvinyl chloride, silicone resin, cycloolefin polymer, and amorphous fluoropolymer. The thermoplastic resin may be melted by heating and mixed with the luminescent nanoparticles, or a polymer ink may be prepared using a solvent and then mixed.
[0074] As the thermosetting resin, an isocyanate compound, a blocked isocyanate compound, an amino resin, a benzoxazine resin, a carbodiimide resin, a cyclocarbonate compound, an epoxy compound, a polyfunctional oxetane compound, an episulfide resin, or the like is used.
[0075] The photocurable resin may be a known photosensitive monomer such as an acryloyl compound, an epoxy compound, a photopolymerizable oligomer, or a photopolymerizable vinyl monomer. These photosensitive monomers may be either radically polymerizable or cationic polymerizable monomers.
[0076] The thermosetting resin may be used alone or in combination of two or more kinds in any ratio.
[0077] In the polymer ink, the weight ratio of the luminescent nanoparticle dispersion to the thermoplastic resin is usually 5.0% by weight or less of the luminescent nanoparticles relative to the thermoplastic resin, preferably 2.0% by weight or less, and more preferably 1.0% by weight or less.
[0078] The polymer ink may contain additives, such as dispersants such as polycarboxylic acid resins, urethane resins, fluororesins, acrylic resins, cycloolefin resins, and derivatives thereof, as well as non-polar solvents, photocuring initiators, polymerization inhibitors, crosslinking agents, and fluorine additives.
[0079] A photocuring initiator is a compound that generates active species such as radicals, cations, or anions upon exposure to light. The excitation energy of the perovskite quantum dots activates the monomers and polymerization proceeds, but adding a photocuring initiator can shorten the exposure time. Specifically, there are many types of initiators, such as organic peroxides, azo compounds, and radical initiators such as triethylborane, nucleophiles such as n-butyllithium, and electrophiles such as monoborane.
[0080] The polymerization inhibitor is a compound that prevents the monomer from unnecessarily polymerizing during storage. Specifically, a hydroquinone compound or the like can be used.
[0081] The crosslinking agent is a compound that modifies the photocurable resin. Specifically, homobifunctional crosslinking agents such as N-hydroxyester compounds, imide ester compounds, and maleimide compounds can be used.
[0082] Fluorine additives are used to impart water repellency to polymer inks or cured resin films by surface modification. Examples of such additives include organic fluorine compounds with perfluoroalkyl groups.
[0083] When the polymer ink is irradiated with excitation light, for example, ultraviolet light with a wavelength of 370 nm, it emits blue to red fluorescent light (wavelength of 450 to 800 nm).
[0084] [Luminescent nanoparticle dispersion material] The luminescent nanoparticle dispersion member of the present invention is formed using the polymer ink. By changing the material and particle size of the luminescent nanoparticles, the wavelength of light absorption can be changed, and high color purity can be achieved, so the luminescent nanoparticle dispersion member is suitable for use in color filters, etc. Furthermore, when the perovskite-type luminescent nanoparticles are metal halide perovskite, they exhibit a high PLQY and a sharp emission spectrum, and are therefore expected to be applied to organic electroluminescence (OLED) materials and next-generation light-emitting device (LED) materials that replace cadmium-based quantum dots. EXAMPLES
[0085] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to the following examples. The synthesis and evaluation methods of FAPbBr3PeQDs (perovskite quantum dots) of Examples 1 to 16 and Comparative Examples 1 to 3 are shown below.
[0086] [Example 1] (1) Preparation of luminescent nanoparticle dispersion (i) Process 1 A precursor solution was prepared by dissolving 75 mg (0.6 mmol) of formamidine hydrobromide (CH4N2·HBr) and 220 mg (0.6 mmol) of lead(II) bromide (PbBr2) in 1 mL of N,N-dimethylformamide (DMF). As a non-polar solvent, 300 μL (0.95 mmol) of oleic acid and 26 μL (0.079 mmol) of oleylamine were dissolved in 5 mL of propylene glycol monomethyl ether acetate (PGM-Ac). The non-polar solvent was placed in a screw tube, and 0.3 mL of the precursor solution was poured therein while stirring at room temperature under atmospheric pressure, and mixed for 3 minutes to obtain a crude nanoparticle dispersion. 1.35 mL of the crude nanoparticle dispersion was placed in a centrifuge tube, and centrifuged at 16,500 rpm for 3 minutes using a tabletop centrifuge AS165W (manufactured by AS ONE Corporation), and the supernatant was removed to obtain crude nanoparticles.
[0087] (ii) Process 2 The crude nanoparticles were redispersed by adding 1 mL of hexane as a dispersion medium, and then centrifuged at 16,500 rpm for 2 minutes. The supernatant was collected to obtain a luminescent nanoparticle dispersion.
[0088] (2) Evaluation of luminescent nanoparticle dispersions (i) Concentration measurement The luminescent nanoparticle dispersion was diluted with a dispersion medium, and an integrating sphere was set in a fluorescence spectrophotometer FP-8600 (manufactured by JASCO Corporation; excitation wavelength 370 nm). The luminescent nanoparticle concentration was calculated from the dilution ratio at which the diluted luminescent nanoparticle dispersion had a sample absorptivity of 0.5. The ratio of the concentration of the luminescent nanoparticles to the concentration of FAPbBr3PeQD calculated from the weighed value was defined as the yield (%).
number
[0089] (ii) Difference in dispersion energy (δd sol -δd LN ) 2 The crude nanoparticles obtained in step 1 were subjected to 30 evaluation solvents (octane, tetrahydrofuran, toluene, cyclopentyl methyl ether, methylcyclohexane, o-xylene, butyl benzoate, isoamyl acetate, ethyl benzoate, 2,2,4-trimethylpentane, p-xylene, benzene, n-butyl acetate, cyclohexane, cis-decahydronaphthalene, mesitylene, m-xylene, hexane, ethylene glycol monoethyl ether acetate, dibutyl ether, t The mixture was redispersed by adding 1 mL of a 100% aqueous solution of trans-decahydronaphthalene, diisobutyl ketone, 2-heptanone, cyclohexanone, benzyl alcohol, acetone, PGM-Ac, 1-octanol, methyl ethyl ketone, or 2-butanol. The supernatant was centrifuged at 16,500 rpm for 2 minutes and scored using a fluorescence spectrophotometer FP-8600 (JASCO Corporation; excitation wavelength 450 nm) with a score of 1 for concentrations above the lower limit of measurement (sample absorptivity of 0.5 at a dilution ratio of 1.25) and a score of 0 for concentrations below.
[0090] Next, the Hansen Solubility Parameter was calculated by the Genetic Algorithm Fitting method using the scores of the evaluated solvents using the analysis software HSPiP (version 5.4.08), and the δd LN was calculated. LN-OAm =16.1MPa 0.5 obtained. Dispersion force energy of the dispersion medium δd solwas confirmed from the database (registered data of HSPiP version 5.4.08) and the dispersion energy δd LN-OAm The square of the difference between these values was calculated to be 1.44 MPa. The preparation and evaluation results of the luminescent nanoparticle dispersion are shown in Table 1.
[0091] [Example 2] A luminescent nanoparticle dispersion was obtained under the same conditions as in Example 1, except that the dispersion medium was changed from hexane to cyclohexane. The yield was calculated from the concentration of luminescent nanoparticles using the same procedure as in Example 1, and was found to be 33.6%. sol -δd LN-OAm ) 2 The result was 0.49 MPa. The results are shown in Table 1. The PLQY was measured using an integrating sphere attached to a fluorescence spectrophotometer FP-8600 (JASCO Corporation; excitation wavelength 370 nm), and was found to be 66%. The results are shown in Table 2.
[0092] [Example 3] A luminescent nanoparticle dispersion was obtained under the same conditions as in Example 1, except that the dispersion medium was changed from hexane to o-xylene. The yield was calculated from the concentration of the luminescent nanoparticles using the same procedure as in Example 1, and was found to be 10.1%. sol -δd LN-OAm ) 2 The result is shown in Table 1.
[0093] [Example 4] A luminescent nanoparticle dispersion was obtained under the same conditions as in Example 1, except that the dispersion medium was changed from hexane to chloroform. The yield was calculated from the concentration of the luminescent nanoparticles using the same procedure as in Example 1, and was found to be 15.3%. sol -δd LN-OAm ) 2 The result is shown in Table 1.
[0094] [Example 5] Crude nanoparticles were obtained under the same conditions as in step 1 of Example 1, except that the organic base compound was changed from 26 μL (0.079 mmol) of oleylamine to 12.5 μL (0.079 mmol) of 4-phenylbutylamine. Next, under the same conditions as in step 2 of Example 1, a luminescent nanoparticle dispersion liquid was obtained. The yield was calculated from the concentration of the luminescent nanoparticles using the same procedure as in Example 1, and was found to be 26.3%. The crude nanoparticles obtained in step 1 were used in the same manner as in Example 1 to measure the δd of the luminescent particles using 32 types of evaluation solvents (octane, tetrahydrofuran, toluene, cyclopentyl methyl ether, methylcyclohexane, o-xylene, butyl benzoate, isoamyl acetate, ethyl benzoate, 2,2,4-trimethylpentane, p-xylene, benzene, n-butyl acetate, cyclohexane, cis-decahydronaphthalene, mesitylene, m-xylene, hexane, ethylene glycol monoethyl ether acetate, dibutyl ether, trans-decahydronaphthalene, diisobutyl ketone, cyclohexanone, benzyl alcohol, anisole, acetone, PGM-Ac, 1-octanol, methyl ethyl ketone, 1,2-dimethoxyethane, ethyl acetate, and 2-butanol). LN was calculated. LN-4PBAm =16.2MPa 0.5 and (δd sol -δd LN-4PBAm ) 2 The result was 1.69 MPa. The results are shown in Table 1.
[0095] [Example 6] A luminescent nanoparticle dispersion was obtained under the same conditions as in Example 5, except that the dispersion medium was changed from hexane to cyclohexane. The yield was calculated from the concentration of luminescent nanoparticles using the same procedure as in Example 1, and was found to be 37.6%. sol -δd LN-4PBAm ) 2 The result is shown in Table 1.
[0096] [Example 7] A luminescent nanoparticle dispersion was obtained under the same conditions as in Example 5, except that the dispersion medium was changed from hexane to PGM-Ac. The yield was calculated from the concentration of the luminescent nanoparticles using the same procedure as in Example 1, and was found to be 20.8%. sol -δd LN-4PBAm ) 2 The result is shown in Table 1.
[0097] [Example 8] Crude nanoparticles were obtained under the same conditions as in step 1 of Example 1, except that the organic base compound was changed from oleylamine 26 μL (0.079 mmol) to octylamine 13.0 μL (0.079 mmol) and the dispersion medium was changed from hexane to methylcyclohexane. Next, under the same conditions as in step 2 of Example 1, a luminescent nanoparticle dispersion liquid was obtained. The yield was calculated from the concentration of the luminescent nanoparticles using the same procedure as in Example 1 and was found to be 65.1%. The crude nanoparticles obtained in step 1 were used in the same manner as in Example 1 to measure the δd of the luminescent particles using 34 types of evaluation solvents (octane, toluene, methyl benzoate, cyclopentyl methyl ether, methylcyclohexane, o-xylene, butyl benzoate, isoamyl acetate, ethyl benzoate, 2,2,4-trimethylpentane, p-xylene, benzene, n-butyl acetate, cyclohexane, cis-decahydronaphthalene, mesitylene, m-xylene, hexane, ethylene glycol monoethyl ether acetate, dibutyl ether, trans-decahydronaphthalene, diisobutyl ketone, 2-heptanone, cyclohexanone, benzyl alcohol, anisole, acetone, PGM-Ac, 1-octanol, methyl ethyl ketone, 1,2-dimethoxyethane, ethyl acetate, 1,4-dioxane, and 2-butanol). LN was calculated. LN-OcAm =16.2MPa 0.5 and (δd sol -δd LN-OcAm ) 2 The result was 0.04 MPa. The results are shown in Table 1.
[0098] [Example 9] A luminescent nanoparticle dispersion was obtained under the same conditions as in Example 8, except that the dispersion medium was changed from hexane to a mixed solvent of cyclohexane / toluene (50:50 vol / vol). The yield was calculated from the concentration of the luminescent nanoparticles using the same procedure as in Example 1, and was found to be 24.5%. sol -δd LN-OcAm ) 2 The result is shown in Table 1.
[0099] [Example 10] A luminescent nanoparticle dispersion was obtained under the same conditions as in Example 8, except that the dispersion medium was changed from hexane to a toluene / methylcyclohexane mixed solvent (50:50 vol / vol). The yield was calculated from the concentration of the luminescent nanoparticles using the same procedure as in Example 1, and was found to be 25.3%. sol -δd LN-OcAm ) 2 The result is shown in Table 1.
[0100] [Example 11] Crude nanoparticles were obtained under the same conditions as in step 1 of Example 1, except that the organic base compound was changed from 26 μL (0.079 mmol) of oleylamine to 9.0 μL (0.079 mmol) of cyclohexylamine and the dispersion medium was changed from hexane to o-xylene. Next, under the same conditions as in step 2 of Example 1, a luminescent nanoparticle dispersion liquid was obtained. The yield was calculated from the concentration of the luminescent nanoparticles using the same procedure as in Example 1, and was found to be 15.4%. The crude nanoparticles obtained in step 1 were used in the same manner as in Example 1 to measure the δd of the luminescent particles using 32 types of evaluation solvents (octane, tetrahydrofuran, toluene, cyclopentyl methyl ether, methylcyclohexane, o-xylene, butyl benzoate, isoamyl acetate, 2,2,4-trimethylpentane, p-xylene, benzene, n-butyl acetate, cyclohexane, cis-decahydronaphthalene, mesitylene, m-xylene, hexane, ethylene glycol monoethyl ether acetate, dibutyl ether, trans-decahydronaphthalene, diisobutyl ketone, cyclohexanone, benzyl alcohol, anisole, acetone, PGM-Ac, 1-octanol, methyl ethyl ketone, 1,2-dimethoxyethane, ethyl acetate, 1,4-dioxane, and 2-butanol). LN was calculated. LN-CAm =16.2MPa 0.5 and (δd sol -δd LN-CAm ) 2 The result was 2.56 MPa. The results are shown in Table 1.
[0101] [Example 12] Crude nanoparticles were obtained under the same conditions as in step 1 of Example 1, except that the organic base compound was changed from 26 μL (0.079 mmol) of oleylamine to 17 μL (0.079 mmol) of dodecylamine. Next, under the same conditions as in step 2 of Example 1, a luminescent nanoparticle dispersion liquid was obtained. The yield was calculated from the concentration of the luminescent nanoparticles using the same procedure as in Example 1, and was found to be 15.8%. The crude nanoparticles obtained in step 1 were subjected to the same procedure as in Example 1 using 33 types of evaluation solvents (octane, toluene, methyl benzoate, cyclopentyl methyl ether, methylcyclohexane, o-xylene, butyl benzoate, ethyl benzoate, 2,2,4-trimethylpentane, p-xylene, benzene, n-butyl acetate, cyclohexane, cis-decahydronaphthalene, mesitylene, m-xylene, hexane, ethylene glycol monoethyl ether acetate, dibutyl ether, trans-decahydronaphthalene, diisobutyl ketone, 2-heptanone, cyclohexanone, benzyl alcohol, anisole, acetone, PGM-Ac, 1-octanol, methyl ethyl ketone, 1,2-dimethoxyethane, ethyl acetate, 1,4-dioxane, 2-butanol) to measure the δd of the luminescent particles. LN was calculated. LN-DAm =16.3MPa 0.5 and (δd sol -δd LN-DAm ) 2 The result was 1.96 MPa. The results are shown in Table 1.
[0102] [Example 13] Crude nanoparticles were obtained under the same conditions as in step 1 of Example 1, except that the organic base compound was changed from 26 μL (0.079 mmol) of oleylamine to 10 μL (0.079 mmol) of 2-phenylethylamine and the dispersion medium was changed from hexane to cyclohexane. Next, under the same conditions as in step 2 of Example 1, a luminescent nanoparticle dispersion liquid was obtained. The yield was calculated from the concentration of the luminescent nanoparticles using the same procedure as in Example 1, and was found to be 46.0%. The crude nanoparticles obtained in step 1 were subjected to the same procedure as in Example 1 using 33 types of evaluation solvents (octane, tetrahydrofuran, toluene, cyclopentyl methyl ether, methylcyclohexane, o-xylene, butyl benzoate, isoamyl acetate, ethyl benzoate, 2,2,4-trimethylpentane, p-xylene, benzene, n-butyl acetate, cyclohexane, cis-decahydronaphthalene, mesitylene, m-xylene, hexane, ethylene glycol monoethyl ether acetate, dibutyl ether, trans-decahydronaphthalene, diisobutyl ketone, cyclohexanone, benzyl alcohol, anisole, acetone, PGM-Ac, 1-octanol, methyl ethyl ketone, 1,2-dimethoxyethane, ethyl acetate, 1,4-dioxane, 2-butanol) to measure the δd of the luminescent particles. LN was calculated. LN-2PEAm =16.4MPa 0.5 and (δd sol -δd LN-2PEAm ) 2 The result was 0.16 MPa. The results are shown in Table 1.
[0103] [Comparative Example 1] A luminescent nanoparticle dispersion was obtained under the same conditions as in Example 1, except that the dispersion medium was changed from hexane to toluene. The yield was calculated from the concentration of the luminescent nanoparticles using the same procedure as in Example 1, and was found to be 8.1%. sol -δd LN-OAm ) 2 The result is shown in Table 1.
[0104] [Comparative Example 2] A luminescent nanoparticle dispersion was obtained under the same conditions as in Example 1, except that the dispersion medium was changed from hexane to benzene. The yield was calculated from the concentration of the luminescent nanoparticles using the same procedure as in Example 1, and was found to be 3.2%. sol -δd LN-OAm ) 2 The result was 5.29 MPa. The results are shown in Table 1.
[0105] [Comparative Example 3] A luminescent nanoparticle dispersion was obtained under the same conditions as in Example 1, except that the dispersion medium was changed from hexane to chlorobenzene. The yield was calculated from the concentration of the luminescent nanoparticles using the same procedure as in Example 1, and was found to be 3.1%. sol -δd LN-OAm ) 2 The result was 8.41 MPa. The results are shown in Table 1.
[0106] [Example 14] A luminescent nanoparticle dispersion was obtained under the same conditions as in Example 1, except that the dispersion medium was changed from hexane to a mixed solvent of cyclohexane to which oleylamine was added at a concentration of 2.1 mmol / L and oleic acid was added at a concentration of 23.6 mmol / L. The yield was calculated to be 36.1% from the concentration of the luminescent nanoparticles using the same procedure as in Example 1. The PLQY was measured to be 85% using the same procedure as in Example 2. The results are shown in Table 2.
[0107] [Example 15] A luminescent nanoparticle dispersion was obtained under the same conditions as in Example 1, except that the dispersion medium was changed from hexane to a mixed solvent of cyclohexane to which oleylamine was added at a concentration of 6.1 mmol / L and oleic acid at a concentration of 72.5 mmol / L. The yield was calculated to be 37.0% from the concentration of the luminescent nanoparticles using the same procedure as in Example 1. The PLQY was measured to be 85% using the same procedure as in Example 2. The results are shown in Table 2.
[0108] [Example 16] A luminescent nanoparticle dispersion was obtained under the same conditions as in Example 1, except that the dispersion medium was changed from hexane to a mixed solvent of cyclohexane to which oleylamine was added at a concentration of 8.0 mmol / L and oleic acid at a concentration of 94.5 mmol / L. The yield was calculated to be 44.7% from the concentration of the luminescent nanoparticles using the same procedure as in Example 1. The PLQY was measured to be 81% using the same procedure as in Example 2. The results are shown in Table 2.
[0109] [Table 1]
[0110] [Table 2]
[0111] The luminescent nanoparticle dispersion liquid prepared in Comparative Example 1 was diluted with a dispersion medium, and an integrating sphere was set in a fluorescence spectrophotometer FP-8600 (manufactured by JASCO Corporation; excitation wavelength 370 nm) to measure λ PL The average particle size of the primary particles calculated from the above was approximately 13 nm. The particle size distribution of the luminescent nanoparticle dispersion before and after classification was measured using a dynamic light scattering particle size distribution analyzer NANOTRAC FLEX (MICROTRAC MRB) (Figure 4). The particle size distribution before classification shows a peak of about 25 nm for the dispersed state and a peak of about 1000 nm for coarse particles and aggregated particles, but it can be seen that these two are separated by classification. The number-average diameter of the supernatant after classification was 14 nm, which matches the average particle size determined by the fluorescence spectrophotometer, indicating that monodispersed fluorescent nanoparticles were obtained by classification.
[0112] In the perovskite quantum dots of Comparative Examples 1 to 3, re-aggregation and sedimentation occurred after redispersion, resulting in a decrease in yield (Figure 2a). However, in Examples 1 to 10, re-aggregation of nanoparticles was suppressed during sedimentation separation, and coarse particles could be removed, resulting in luminescent nanoparticle dispersions with excellent dispersibility and improved yield (Figure 2b).
[0113] [Luminescent nanoparticle polymer ink] 23.1 g of PMMA and 40 mL of toluene were placed in a screw cap and mixed for 36 hours at 60 rpm using a rotating stand to prepare a polymer solution. 2.5 mL of the luminescent quantum dispersion liquid prepared in Example 14 and Comparative Example 1 was added to 10.9 g of this polymer solution, and the mixture was kneaded for 20 minutes and degassed for 30 seconds using a kneading and degassing machine to obtain two transparent luminescent nanoparticle polymer inks.
[0114] [Luminescent nanoparticle dispersion material] The luminescent nanoparticle polymer ink was uniformly formed on a base film at a coating speed of 50 mm / sec using a multi-film applicator (1806F / 150 manufactured by BEVS) and an auto-film applicator (manufactured by Tester Sangyo Co., Ltd.) with a gap set to 700 μm. The formed body was dried on the auto-film applicator at 70° C. for 20 minutes, and the formed body was peeled off from the base film to obtain a luminescent nanoparticle dispersion member on a film. When the thickness was measured with a digital thickness gauge (PG02A manufactured by Techclock Co., Ltd.), the thickness of both the luminescent nanoparticle dispersion members using the luminescent nanoparticle dispersion liquids of Example 14 and Comparative Example 1 was 130 μm.
[0115] Using a UV-Vis-NIR spectrophotometer V-670 (manufactured by JASCO Corporation), the absorbance of the luminescent nanoparticle dispersion members using the luminescent nanoparticle dispersions of Example 14 and Comparative Example 1 was measured. When comparing at a wavelength of 512 nm, which is the absorption wavelength of perovskite quantum dots, the absorbance of the luminescent nanoparticle member made with the dispersion of Example 14 was about 4.3 times higher than that of Comparative Example 1 (FIG. 5). Furthermore, an integrating sphere was attached to a fluorescence spectrophotometer FP-8600 (JASCO Corporation; excitation wavelength 450 nm) to measure the fluorescence intensity of the luminescent nanoparticle dispersion members using the luminescent nanoparticle dispersion liquids of Example 14 and Comparative Example 1. When the maximum values of the fluorescence spectra were compared, the absorbance of the luminescent nanoparticle member made with the dispersion liquid of Example 14 was approximately 4.4 times greater than that of Comparative Example 1. This is because the yield in Example 14 and Comparative Example 1 was about 4.5 times higher, and the concentration of fluorescent nanoparticles in the light conversion member was increased, resulting in increased absorbance and emission spectrum.
[0116] Luminescent nanoparticle dispersion members convert incident light into wavelengths specific to fluorescent nanoparticles and are used in optical devices. If a large amount of incident light without wavelength conversion is transmitted, the appearance changes due to color mixing. By improving the dispersibility of fluorescent nanoparticle dispersion liquid and increasing its concentration, it has become possible to create luminescent nanoparticle dispersion members with a high optical density of incident light. [Industrial Applicability]
[0117] The luminescent nanoparticle dispersion according to the present invention, specifically the perovskite quantum dots, exhibits dispersion stability and a high PLQY, and therefore can be used as a luminescence and light conversion material with excellent optical and physical properties in a wide range of fields, such as next-generation displays and agricultural films.
Claims
1. A step 1 of synthesizing a crude nanoparticle solution in liquid phase by mixing a luminescent nanoparticle precursor, an organic base compound, and an organic acid compound in an organic solvent, and then removing the organic solvent from the crude nanoparticle solution by sedimentation to obtain crude nanoparticles; The dispersion force energy (δd Sol ) and the dispersion energy of the luminescent nanoparticles (δd LN ) and the square of the difference (δd Sol -δd LN ) 2 and step 2 of adding a dispersion medium having a viscosity of 3.0 MPa or less to redisperse the coarse nanoparticles, and then removing coarse particles by classification.
2. 2. The method for producing a luminescent nanoparticle dispersion liquid according to claim 1, wherein in the step 2, one or more of an organic base compound, an organic acid compound, and a metal halide are dissolved in the dispersion medium.
3. 3. The method for producing a luminescent nanoparticle dispersion liquid according to claim 1, wherein the dispersion medium in the step 2 is a non-polar solvent having an alicyclic hydrocarbon skeleton.
4. 3. The method for producing a luminescent nanoparticle dispersion liquid according to claim 1, wherein the non-polar solvent having an alicyclic hydrocarbon skeleton is one or more of cyclohexane, methylcyclohexane, and decalin.
5. 3. The method for producing a luminescent nanoparticle dispersion liquid according to claim 1, wherein the luminescent nanoparticles are metal halide perovskite.
6. 3. The method for producing a luminescent nanoparticle dispersion liquid according to claim 1, wherein the luminescent nanoparticles have a particle size of 1 to 30 nm.
7. A luminescent nanoparticle polymer ink, comprising a luminescent nanoparticle dispersion liquid obtained by the method according to claim 1 or 2, and a polymer dissolved therein.
8. A luminescent nanoparticle dispersion member formed by using the luminescent nanoparticle polymer ink according to claim 7.
Citation Information
Patent Citations
Modified pigments and use thereof
JP2019026835A
Pasty resin composition, high heat-conductive material, and semiconductor device
JP2022018051A